The Essence Of Heterogeneity Of Organizational Behavior In Educational Institutions - Andriani, Rini; Abidin, Zaenal; Jasmine, Nadia; Sari, Eliana; Karnati, Neti (Jurnal Edusci, 2024)
This study aims to describe the essence of heterogeneity of organizational behavior in educational institutions. This research uses a literature study method by observing various documents from books and journals. The literature study focuses on researching literature related to the essence of heterogeneity of organizational behavior in educational institutions and democratic leadership. Data collection is carried out by collecting literature data, reading, recording, and managing research results objectively, systematically, analytically, and critically by looking at the year of publication and the most up-to-date research. The results of this study show that the existence of cultural backgrounds caused by differences between regions affects the way of thinking, attitudes, work styles, and communication styles of each individual and must be managed using strong motivation through work appreciation, recognition, and salary, strong leadership, and minimizing conflicts. Democratic leadership has a role in determining the success of an educational institution because this leadership provides a proportionate space for subordinates to be involved in the institution's progress. The heterogeneity of organizational behavior is inevitable in organizations, so it must be appropriately managed. This management requires organizational leadership so subordinates feel valued and improve their performance to advance educational institutions.